Recent advances in in silico design and characterization of superalkali-based materials and their potential applications: A review - Pandey, Sarvesh Kumar; Arunan, Elangannan; Das, Ratnesh; Roy, Atish; Mishra, Arunesh Kumar (Frontiers in Chemistry, 2022)
In the advancement of novel materials, chemistry plays a vital role in developing the realm where we survive. Superalkalis are a group of clusters/molecules having lower ionization potentials (IPs) than that of the cesium atom (3.89 eV) and thus, show excellent reducing properties. However, the chemical industry and material science both heavily rely on such reducing substances; an in silico approach-based design and characterization of superalkalis have been the focus of ongoing studies in this area along with their potential applications. However, although superalkalis have been substantially sophisticated materials over the past couple of decades, there is still room for enumeration of the recent progress going on in various interesting species using computational experiments. In this review, the recent developments in designing/modeling and characterization (theoretically) of a variety of superalkali-based materials have been summarized along with their potential applications. Theoretically acquired properties of some novel superalkali cations (Li3+) and C6Li6 species, etc. for capturing and storing CO2/N2 molecules have been unveiled in this report. Additionally, this report unravels the first-order polarizability-based nonlinear optical (NLO) response features of numerous computationally designed novel superalkali-based materials, for instance, fullerene-like mixed-superalkali-doped B12N12 and B12P12 nanoclusters with good UV transparency and mixed-valent superalkali-based CaN3Ca (a high-sensitivity alkali-earth-based aromatic multi-state NLO molecular switch, and lead-founded halide perovskites designed by incorporating superalkalis, supersalts, and so on) which can indeed be used as a new kind of electronic nanodevice used in designing hi-tech NLO materials. Understanding the mere interactions of alkalides in the gas and liquid phases and the potential to influence how such systems can be extended and applied in the future are also highlighted in this survey. In addition to offering an overview of this research area, it is expected that this review will also provide new insights into the possibility of expanding both the experimental synthesis and the practical use of superalkalis and their related species. Superalkalis present the intriguing possibility of acting as cutting-edge construction blocks of nanomaterials with highly modifiable features that may be utilized for a wide-ranging prospective application.